(m1,m2)-pseudo almost periodic solutions of Clifford-valued high-order fuzzy cellular neural networks with time delays - Bing Li; Ting Chen; Yongkun Li (Franklin Open)
This article mainly focuses on exploring the pseudo periodic dynamics of a class of Clifford-valued high-order fuzzy cellular neural networks (FCNNs) using non decomposition methods. By utilizing fixed point theorems, inequality techniques, and contradiction methods, the existence and stability of pseudo periodic solutions for this type of neural network (NN) were obtained. When the system considered in this article degenerates into a real-valued NN, the results of this article are also new. At the same time, we used numerical examples to confirm the effectiveness of the results presented in this paper.